Precambrian reidite discovered in shocked zircon from the Stac Fada impactite, Scotland - Reddy, S.; Johnson, T.; Fischer, S.; Rickard, W.; Taylor, Richard (GEOLOGICAL SOC AMER, INC, 2015)
Terrestrial impact events have had a profound influence on Earth’s geological, geochemical, and biological evolution. However, the record of Precambrian impacts is poorly constrained due to the dynamic nature of plate tectonics, erosion, and deposition of younger rocks that may destroy or cover the evidence. Here we report the first Precambrian occurrence of the rare mineral reidite (ZrSiO4) within grains of shocked zircon in the ca. 1.18 Ga Stac Fada Member (Stoer Group), northwestern Scotland. The reidite, preserved as <2-µm-wide lamellae, is unambiguous evidence of shock pressures in excess of ∼30 GPa and confirms the impact origin for the Stac Fada deposit. The reidite lamellae are locally deformed, and sites of deformation record its decomposition to baddeleyite (ZrO2) and amorphous silica, the first natural example of this transformation. The findings demonstrate that reidite and baddeleyite may form and be transported in high-energy ejecta without physical or chemical breakdown and are stable during sedimentary diagenesis and low-grade metamorphism. Thus, reidite may be preserved over time scales exceeding 1 b.y., establishing the use of reidite within detrital shocked zircon from Precambrian strata as a viable and valuable means of recognizing and characterizing ancient terrestrial impact events.